Reduction of TRAF3 by heterozygosity or aging impacts B cell function - Emma L. Hornick; Kyp Oxley; Nathaniel Wieting; Emma Treco; Bruce S. Hostager; Gail A. Bishop (Proceedings of the National Academy of Sciences, 2025)
TNF receptor-associated factor 3 (TRAF3) is a signaling adaptor protein that is ubiquitously expressed but has highly distinct cell type–specific functions. TRAF3 plays critical roles in restraint of B lymphocyte activation, differentiation, and homeostatic survival. Consistent with such roles, loss-of-function mutations in TRAF3 have long been found in various human B cell malignancies. Mice lacking TRAF3 specifically in B cells have autoimmune manifestations, lymphadenopathy, and increased incidence of B cell lymphomas. More recently, human patients with germline TRAF3 mutations leading to haploinsufficiency have been reported; the phenotypes of these patients show striking similarities with those of mice with TRAF3-deficient B cells. This raises the important knowledge gap of how relative quantity of TRAF3 protein regulates B cells. To address this question, we investigated the effect of decreased B cell TRAF3 using mice whose B cells are heterozygous for loss of Traf3 . Traf3 +/− B cells displayed multiple functional abnormalities, to an extent intermediate between Traf3 +/+ and Traf3 −/− B cells, indicating a striking dose–response of B cells to relative quantities of TRAF3. Additionally, B cell TRAF3 protein—but not transcript—was reduced in B cells from normal aged mice and humans, consistent with increased occurrence of both B cell hyperactivity and B cell malignancies in older populations. Treatment of aged mice with a proteasome inhibitor restored the level of B cell TRAF3, suggesting age-related chronic signaling through receptors that lead to TRAF3 degradation. Thus, relative levels of B cell TRAF3 protein have important biological impacts on B cell function.